2015
DOI: 10.1016/j.sajb.2015.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Quality and antioxidant activity of rice grown on alluvial soil amended with Zn, Cu and Mo

Abstract: Insufficient micronutrients are a common phenomenon in Malaysian soils derived from riverine alluvium, which affect the growth and quality of rice. A study was conducted on such soils at Kelantan, Malaysia to evaluate the effects of applying Zn (5 kg ha −1 ),Cu (4 kg ha −1 ) and Mo (0.5 kg ha −1 ) along with the recommended N, P, K and S at 120, 30, 50, 10 kg ha −1 , respectively on rice plant growth, grain yield, quality and antioxidant activity. Any single micronutrient or in combination with macronutrients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…The highest IC50 value for reducing power observed in Jalal Abad-14 (29.28 mg/ml), whilst the lowest was revealed in Sha Lawangi (10.06 mg/ml). The current finding indicates that genetic variation, soil types and environmental conditions may have contributed to the antioxidant capacity of varieties and the data suggests that the varieties have moderate antioxidant activity [22,23]. The relation of AA and other grain properties is shown in Fig.…”
Section: Grain Quality Contentmentioning
confidence: 55%
“…The highest IC50 value for reducing power observed in Jalal Abad-14 (29.28 mg/ml), whilst the lowest was revealed in Sha Lawangi (10.06 mg/ml). The current finding indicates that genetic variation, soil types and environmental conditions may have contributed to the antioxidant capacity of varieties and the data suggests that the varieties have moderate antioxidant activity [22,23]. The relation of AA and other grain properties is shown in Fig.…”
Section: Grain Quality Contentmentioning
confidence: 55%
“…The concentration of Zn was high, with values ranging from 1.2 to 181.0 mg kg −1 . The addition of Zn into the soils during the flood was in a way enhanced their productivity as shown by the study of Panhwar et al [22] who found that rice grown in the soils of the Kelantan Plains responded positively to Zn application. They found that due to Zn application, not only rice yield was increased, but also the quality of its grains was enhanced.…”
Section: To Enhance the Productivity Of Soils In The Affected Areasmentioning
confidence: 96%
“…The reason for this is that the fertility of the soil had been improved somewhat by GML application, which increased the water pH, while the concentration of Al 3+ and/or Fe 2+ was concomitantly reduced. The growth of rice was further enhanced by the increase in Ca, Mg, Zn, and Cu contents [35,38]. Basalt treatment gave low grain yield in the first season, but with time, it increased to that of the GML treatment.…”
Section: Residual Effects Of Gml Basalt With or Without Bio-fertilizmentioning
confidence: 98%